Case study method for new product development in engineer to order organisations - Abdul Rahim, Abd. Rahman; Nabi Baksh, Mohd. Shariff (MCB UP Ltd, 2003)
The case study method has been widely used as a research instrument for data collection to build theory. Reports on the use of case study method for new product development (NPD) in an engineer-to-order (ETO) organization. Discusses previous work on NPD in the literature in order to determine the knowledge gap that exists. Discovers that NPD work in an ETO organization is lacking despite its importance. Proposes a case study method as a tool to bridge this gap. Explains and justifies the reasons for choosing the case study method. Also describes case study design with the case study protocol. Then discusses the execution of the case study, method of analysis and the limitations of case study research. The findings will assist researchers who are interested in pursuing future research work in this area